2005
DOI: 10.1007/s00436-005-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine analogue cytotoxicity against Trypanosoma cruzi

Abstract: Trypanosoma cruzi is the etiological agent of American trypanosomiasis. Most of the available data on trypanosomatid parasites were obtained from African trypanosomes. Parasitic protozoa polyamine metabolism and transport pathways comprise valuable targets for chemotherapy. T. cruzi cannot synthesize putrescine, but its uptake from the extracellular milieu can promote parasite survival. Nevertheless, little is known about the cell biology of this diamine in T. cruzi. Here we notice that the putrescine analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Magnification: A and D, ¾75 000; B ¾40 000; C ¾87 000; E, ¾33 500; F, ¾71 000. The antiproliferative effect of DAB may be due, at least in part, to destruction of mitochondria as reported for spermine analogues (Stevens et al, 1977), consistent with the observed reduction in O 2 consumption in DFMOtreated Trypanosoma brucei (McCann et al, 1981) and with gross mitochondrial ultrastructural alterations in DABtreated T. cruzi (Menezes et al, 2006). We have previously shown that DAB leads to the destruction of the trichomonad redox organelle (Reis et al, 1999), suggesting a conserved mode of action of DAB in unrelated parasitic protozoa.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Magnification: A and D, ¾75 000; B ¾40 000; C ¾87 000; E, ¾33 500; F, ¾71 000. The antiproliferative effect of DAB may be due, at least in part, to destruction of mitochondria as reported for spermine analogues (Stevens et al, 1977), consistent with the observed reduction in O 2 consumption in DFMOtreated Trypanosoma brucei (McCann et al, 1981) and with gross mitochondrial ultrastructural alterations in DABtreated T. cruzi (Menezes et al, 2006). We have previously shown that DAB leads to the destruction of the trichomonad redox organelle (Reis et al, 1999), suggesting a conserved mode of action of DAB in unrelated parasitic protozoa.…”
Section: Discussionsupporting
confidence: 79%
“…The putrescine analogue DAB has been tested in different micro-organisms (Calvo-Méndez et al, 1993;ArteagaNieto et al, 1996;Reis et al, 1999;Garcia et al, 2005;Menezes et al, 2006) and was effective against DFMOresistant parasites (Calvo-Méndez et al, 1993;Reis et al, 1999). DAB has also been shown to be a powerful ODC inhibitor in a number of organisms (Calvo-Méndez et al, 1993;Arteaga-Nieto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously noticed that DAB inhibits the growth of anaerobic trichomonad parasite Tritrichomonas foetus (Reis et al 1999) and T. cruzi (Menezes et al 2006), but little is known about the role of putrescine in Giardia cell biology. Here, we examined the effects of DAB in G. lamblia trophozoite proliferation, differentiation, ultrastructure, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not effective against Leishmania or T. cruzi due to differences in the gene and an inability to produce significant amounts of putrescine, respectively [60][61][62][63]. Use of the putrescine analogue 1,4-diamino-2-butanone (DAB) caused inhibition of the proliferation of Leishmania and T. cruzi and severe damage to the mitochondrion characterized by swelling, fenestration and the presence of few cristae [64][65][66][67][68].…”
Section: B E)mentioning
confidence: 99%